MODEL OF NEURAL NETWORKS WITH AN INFINITE NUMBER OF CELLS AND SMALL PARAMETER - Vasilyev, Sergei Anatolevich; Kanzitdinov, Soltan Kanzitdinovich (Современные информационные технологии и ИТ-образование; Том 12 № 2 (2016): Современные информационные технологии и ИТ-образование, 2016)
A method of analysis the dynamics of complex systems using neural networks with an infinite number of cells was investigated. For the Cauchy problem for systems of differential equations of countable order, which describes the neural network with infinite number of cells, considered the question of the existence and uniqueness of its solution.